(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2017)
The aim of the article is an appraisal of local determinants of pomorskie voivodeship for biogas production. The research was conducted for the districts of pomorskie viovodeship based on 2014 data. The analysis was conducted using cluster analysis based on six indicators: share of agricultural land in total land area of the district, grazing livestock per 100 ha of agricultural land, yearly mixed waste collected on 100 km2 and municipal sewage cleaned per 100 km2. Districts of pomorskie voivodeship were divided to four groups based on cluster analysis. The research shows that north-east parts of the region have favorable conditions for biogas production using municipal waste. While in the west and middle part of region show favorable conditions for agricultural biogas production.